JUDGE DISPARITY IN IMPOSING SANCTIONS AGAINST JUSTICE COLLABORATORS: Case Study of Decision Number 1031/Pid.B/2022/Pn.Mks and Decision Number 798/Pid.B/2022/Pn.Jkt.Sel - Nuroini, Indi; Damajanti, Dr. Sisca Utami; Djalil, Mochamad; Aprilia, Denna (jfpublisher, 2024)
Premeditated murders are quite challenging to obtain additional statements as there are generally no witnesses at the crime scene. However, the perpetrators have already planned to eliminate possible witnesses. Therefore, the role of the perpetrator’s witness (justice collaborator) is very important in the investigation process and court decision. According to the Criminal Code, the legal subject of the case is a “person” (for example, in article 340 of the Criminal Code, it is referred to as “anyone,” which means a specific individual). This research aims to understand the role of justice collaborators in sanction decisions by judges and analyze the differences in judges’ decisions through a study of two decisions: 103/Pid.B/2022/Pn.Mks and 798/Pid.B/2022/Pn.Jkt.Sel. This research used normative approach, relying on secondary data such as laws, court decisions, and legal theories. This research showed that there is no specific regulation on sanctions for a justice collaborator (witness who cooperates with law enforcement) in Indonesia. Judges have the flexibility to consider the sanctions imposed on justice collaborators, so there are often differences in punishment even though the offenses are the same. Justice collaborators get an advantage in law if they help law enforcement officials solve criminal cases.